Analisis Peraturan Daerah No. 9 Pasal 3 tahun 2014 Tentang Pembinaan Anak Jalanan, Gelandangan, Pengemis dan Pengamen Dalam Tinjauan Siayasah Dusturiyah - Rifky Arfandy Syam Lambi (Institut Agama Islam (IAIN) Kendari, 2023)
This study aims to determine the implementation of Regional Regulation Number 9 of 2014 concerning the Development of Street Children, Vagrants, Beggars and Buskers on review Siyasah Dusturiyah's. The results of this study are in the form of implementing regional regulation number 9 of 2014, namely guidance or education provided by the social service to street children, vagrants, beggars and also buskers, then further empowerment programs in the form of assistance that are no less important than the form of education to the community in the form of banners or billboards, stickers on the road and the like, and also rehabilitation programs carried out by social services in fostering street children through cooperation with LKSA (children's social welfare institution). The view of the siyasa dusturiyah towards regional regulation number 9 of 2014 is in accordance with what was determined by the Kendari regional government in the form of the concept of constitution, legislation, syuro/democracy, and ummah.